A STUDY OF ASYNONYMY: MUHAMMAD SHAHRUR'S ALTERNATIVE INTERPRETATION OF QS. AL-NŪR (24): 3 - Novita, Ida; Halimatussa'diyah, Halimatussa'diyah; Apriyanti, Apriyanti (Peminat Ilmu Ushuluddin, 2024)
This study examines the principle of asynonymy—the idea that every word in the Qur’an possesses a distinct and non-interchangeable meaning—within the hermeneutical framework of Muhammad Shahrur, a contemporary Islamic thinker known for his reformist and modernist approach to Qur’anic interpretation. The focal point of this research is Surah An-Nur verse 3, exploring how Shahrur’s semantic method offers a significantly different reading from traditional exegetical understandings. While classical interpretations often view this verse as a moral and legal prohibition against marriage between fornicators and polytheists, Shahrur reinterprets the terms zānī, zāniyah, and mushrik as having specific, non-synonymous meanings. He argues that these terms reflect broader ethical concerns such as mutual consent, human dignity, and interpersonal integrity, rather than rigid legal or theological classifications. This reinterpretation carries far-reaching implications for Islamic ethics, particularly in the realms of sexual conduct, social justice, and gender equality. By engaging in a critical dialogue between classical tradition and contemporary thought, this study demonstrates how linguistic precision can open new pathways for understanding the Qur’an in ways that are socially and ethically relevant in the modern context.